The severe epilepsy syndromes of infancy: A population‐based study. (21st January 2021) - Howell, Katherine B.; Freeman, Jeremy L.; Mackay, Mark T.; Fahey, Michael C.; Archer, John; Berkovic, Samuel F.; Chan, Eunice; Dabscheck, Gabriel; Eggers, Stefanie; Hayman, Michael; Holberton, James; Hunt, Rodney W.; et al.
Abstract: Objective: To study the epilepsy syndromes among the severe epilepsies of infancy and assess their incidence, etiologies, and outcomes. Methods: A population‐based cohort study was undertaken of severe epilepsies with onset before age 18 months in Victoria, Australia. Two epileptologists reviewed clinical features, seizure videos, and electroencephalograms to diagnose International League Against Epilepsy epilepsy syndromes. Incidence, etiologies, and outcomes at age 2 years were determined. Results: Seventy‐three of 114 (64%) infants fulfilled diagnostic criteria for epilepsy syndromes at presentation, and 16 (14%) had "variants" of epilepsy syndromes in which there was one missing or different feature, or where all classical features had not yet emerged. West syndrome (WS) and "WS‐like" epilepsy (infantile spasms without hypsarrhythmia or modified hypsarrhythmia) were the most common syndromes, with a combined incidence of 32.7/100 000 live births/year. The incidence of epilepsy of infancy with migrating focal seizures (EIMFS) was 4.5/100 000 and of early infantile epileptic encephalopathy (EIEE) was 3.6/100 000. Structural etiologies were common in "WS‐like" epilepsy (100%), unifocal epilepsy (83%), and WS (39%), whereas single gene disorders predominated in EIMFS, EIEE, and Dravet syndrome. Eighteen (16%) infants died before age 2 years. Development was delayed or borderline in 85 of 96 (89%) survivors, being severe–profound in 40 of 96 (42%). All infants with EIEE or EIMFS had severe–profound delay or were deceased, but only 19 of 64 (30%) infants with WS, "WS‐like, " or "unifocal epilepsy" had severe–profound delay, and only two of 64 (3%) were deceased. Significance: Three quarters of severe epilepsies of infancy could be assigned an epilepsy syndrome or "variant syndrome" at presentation. In this era of genomic testing and advanced brain imaging, diagnosing epilepsy syndromes at presentation remains clinically useful for guiding etiologic investigation, initial treatment, and prognostication.